REKAYASA DESAIN CIRCULAR HYBRID CRASH BOX UNTUK PENINGKATAN PERFORMA KELAYAKAN TABRAK - Wakhidah, Delia Hani; Choiron, Moch. Agus; Irawan, Yudy Surya (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
In previous studies, hybrid crash boxes have been developed because it show better energy absorption characteristics. Circular hybrid crash box combine the advantages of low-density of composite with stable deformation of metal provide a potential energy absorption device. Tests were carried out experimentally and iumerically under frontal load. This study aims to determine the energy absorption characteristics of two different configuration of hybrid material compositions using Aluminum Alloy 6063 and T300-epoxy Carbon Fiber composites. Present two typical configurational schemes, namely Al-Ko (i.e. a metal outer tube internally filled with an inner carbon fiber reinforced plastic (CFRP) tube) and Ko-Al (i.e. an outer composite tube internally filled with an inner metal tube). Composite layups arrangement with fiber orientation direction [0,90]10. First, the simulation models were developed and validated by comparing the damage modes and crashworthiness indictors with the dedicated experimental study. Second, the interactive effects of different configuration hybrid tubes were investigated by analyzing the discrepancies in the deformation pattern and internal energy absorption of each material through the validated simulation models. The test results show that the greatest energy absorption occurs in the Al-Ko model of 7401.4 J. This hybrid crash box has an energy absorption value of 11% greater compared to the sum of the energy absorption of aluminum tubes (3746.5 J) and composite tubes (2923.4 J).